Pengaruh Budaya Organisasi, Kemampuan Kerja dan Perputaran Karyawan terhadap Produktivitas Kerja di Gudang Logistik PT. P - Dian Ramadani; Mardatillah Mardatillah; Sani Gazali; Mira. S (Jurnal Manajemen Bisnis Digital Terkini, 2025)
P is a company engaged in logistics which is located at km 13 in the city of Balikpapan. PT. P focuses on the automotive, mining, oil and gas, materials and knowledge industries, fast-moving consumer goods (FMCG), electronics and technology, food and beverages, and e- commerce. In the PT. P department productivity is often not achieved due to the many problems that occur that hinder the company's target standards. The purpose of this research is to find out what factors can affect work productivity at PT. P department. There are several factors that can affect work productivity, including organizational culture, work ability and employee turnover. This study uses primary data and secondary data. The method used is a quantitative method.The results showed that there was a significant positive effect between organizational culture on work productivity, there was a significant positive effect between work ability on work productivity, and there was a significant positive effect between employee turnover on work productivity. The results of the F and regression tests found that there was an influence of 37.1% organizational culture, work ability and employee turnover together on work productivity and the remaining 62.9% was influenced by other variables.